ANALISIS KEKUATAN TEKANAN PAVING BLOK LIMBAH PLASTIK HIGH DENSITY POLYETHYLENE (HDPE), Dan POLYETHYLENE - Aulia Aldianor; Andy Mizwar; Rijali Noor; Muhammad Abrar Firdausy (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
The use of plastic is increasing as the population increases, while plastic has properties that are difficult to decompose, efforts are needed to reduce plastic waste into other useful products. One alternative that is used is to make plastic waste into a mixture of paving blocks, which is a purpose of this resarch. In this studi using descriptive data analysis. . In this study using descriptive data analysis. In this study, paving blocks were used with a mixture of High Density Polyethylene (HDPE) & Polyethylene Terephthalate(PET) plastic waste and additional used oil as fuel and thinner. To obtain 1 paving block made from plastic waste, it takes 2 kg of plastic with a composition ratio of 1.4 kg HDPE, 0.6 kg PET plastic, and 0.66 L used oil. The rasults of the compresive strength test of the 3 paving blocks obtained an average value of 11.37 MPa, then based on the quality requirements based on SNIi 03-0691-1996 they met the requirements and entered the D quality category for garden and sidewalk purposes.